Entrepreneurial Community Extension Capabilities of the College of Business - Ramos, Raquel (Social Sciences and Development Review, 2017)
This study reviewed the capabilities of the College of Business-PUP topromote or hasten entrepreneurial development through technology transfer to the local communities (barangay) that they adopted as part of its community extension program. The researcher used the descriptive  research design, with two sets of survey questionnaires: one to get the profile of the 17 faculty members who handle entrepreneurship or entrepreneurial-related subjects in the College of Business (CB) of the Polytechnic University of the Philippines (PUP), and the other to determine the perception of 24 barangay participants on the effectiveness/relevancy of community extension projects of the College. Percentages, arithmetic mean and standard deviation (for measure of dispersion) were computed to describe the data, particularly those that were related to the profile of respondent faculty members. Chi-square analysis with the use of contingency table was employed for hypotheses that involved measure of associations, like the entrepreneurial traits of the faculty members and their profile variables. Correlation coefficient was computed, and inputs were tested for 5% level of significance. Tests for significance of data relating to the community extension project were conducted using two-sample t-test and ANOvA.The study revealed that the College of Business has the legal mandate and adequate policy support to provide entrepreneurial development-related program (formal education) and embark on community extension programs/projects (nonformal education); and there is an existing institutional structures responsible for the development, implementation and coordination of education program and community extension program. The study also showed that the present program offerings are employee culture-oriented rather than self-employed culture oriented, and have a strong foundation on business core courses (subjects), but are wanting in entrepreneurial core courses such as start-up courses; courses that would provide students a broad-based understanding of the private sector particularly MSMes; courses and instructional methods that would allow active involvement (practical exposure) in new and emerging ventures; action-based instructional materials; and courses that develop well-defined entrepreneurial traits, skills, and competencies that must be acquired by students upon graduation.Results of the study showed the profile of typical faculty in the College of Business: a female, 48 years old, married, master’s degree holder, with 17 years of work experience in the academe and with less than three years of involvement in community extension projects. This highlights the increasing and dominant role of women, both experienced and educationally prepared, in academic institutions. The study revealed that the business academics sector is aging and many are about to retire. The study also found that the respondent faculty members, in general, perceived themselves to have all the entrepreneurial traits although in varying degree of possession, moderate to high, and those with work experience outside the academe have a higher level of educational attainment than those without experience outside the academe.This study showed that the entrepreneurial thrust, duration of the program, logistics, venue and relevance of subject matter were positively perceived to be effective and relevant to respondent participants’ entrepreneurial development. Moreover, respondent participants perceive the resource person/s in the extension projects to be credible, capable of establishing rapport with participants and using effective methodologies.
Keywords: entrepreneur; knowledge workers; community extension; barangays; capabilities; MSMes